THE JOY AND PAIN OF LIVING IN THE INDIAN VILLAGE - R. C. Sekhar (2000)
This paper presents a normative vision of a joyous community in rural India where more than 70 per cent of Indians live. It is no different from the utopian vision of Professor Ostrom of communities where everyone will do unto others what they would want done to themselves. This paper derives inspiration from a long history of moral philosophies and, more particularly, from Indian traditions. Contrasting this "ought to be" with "what is" India today, it describes the intentions of the constitution makers in India who derived their inspiration from the French Revolution, the U.S. Bill of Rights, and the Soviet Revolution. They were chary of furthering "decentralization" due to fears that autonomous villages with ancient caste conflicts would stifle the already oppressed. Conflict resolution mechanisms were centralized hoping that this would protect the weak. Affirmative action was enshrined in the constitution and so were polemics and debates institutionalized. Democratic discourse and reconciliation were not, however, institutionalized. Universal and uniform laws were sought. Recent efforts at decentralization have used constitutional methods, cooperative structures, and several other artifacts. There were misgivings about the ability of the Indian village to fit and adapt its ancient methods and values to these `liberal' traditions of the constitution. This paper describes empirical evidence to show that the process of adaptation has taken root. These evidences are in micro-level studies and more extensive field surveys reported in recent research. The author's own research uses instruments and methods to "measure culture" and triangulate the results with other methods. The author suggests the next steps to be taken for bringing more joy to the Indian villages and for reducing their pain. Among other conceptual measures, this paper shows that the eaning and manner of democratic participation and the utility of "market systems" need major clarifications and elucidation. Major changes in incorporating self-governance in police and judicial administration are also proposed. All these will go towards reducing transaction costs